Increasing the build rate of high-strength aluminium alloys produced by laser powder bed fusion. (June 2023) - Del Guercio, Giuseppe; Simonelli, Marco
Highlights: A pathway to increase the build rate of AA2024 produced by l -PBF is proposed. Build rate of highly dense parts is increased by varying process parameters based on melt pool geometry. Defects-free samples can be fabricated with an increase of build rate of 150%. The hardness of the specimens is not affected by the increase in build rate. Abstract: Aluminium alloys from the 2xxx series represent important structural materials due to their optimal combination of strength and corrosion resistance. However, their production by means of laser powder bed fusion (PBF-LB/M) is hampered by the presence of detrimental pores and hot cracks. These defects can be mitigated with appropriate process parameters investigations, often at the expense of the build rate. In this study, a combination of modelling and experimental work is adopted to predict the consolidation behaviour of AA2024, a well-known high-strength Al alloy, in regimes characterised by a progressive increase of build rate. The melt pool geometries are predicted as a function of various process parameters using the Rosenthal solution and variable values of absorptivity. This leads to a facile production of near-full dense crack-free parts at an increasing build rate. The analysis of the specimens produced with such processing parameters reveals that the microstructural features and mechanical properties of AA2024 are largely preserved when build rate is increased. Our approach can be easily implemented in standard PBF-LB/M systems as it does not rely on machine adaptations. Therefore, our new proposed approach might result in a practical solution to increase the productivity of other high-strength Al-alloys in industrial settings.